The linguistic landscapes of Kyzyl and Ulan-Ude as a mirror of regional language policy - Khilkhanova, Erzhen V.; Ondar, Choigan G.; Ivanov, Viacheslav V.; Hakobyan, Karen S. (The New Research of Tuva, 2024)
The article is dedicated to the comparative study of the linguistic landscapes of Kyzyl and Ulan-Ude, and the functioning of the official languages in Tuva and Buryatia in them. This work is based on a mixed methodology that includes the analysis of official documents regulating language policy in both republics, and the analysis of visual textual information such as signage, signs, and announcements from public institutions and private organizations. The information was collected using the method of total fixation in the central and suburban areas of both capital cities.The analysis revealed the dominance of Russian and the secondary significance of Tuvan and Buryat in the linguistic landscapes. This can be seen both in the relatively small number of inscriptions in these languages and in their design, with smaller inscriptions and a more restricted location. There are also violations of the laws regarding languages in the Republics of Tuva and Buryatia. Spelling and other errors are also recorded in inscriptions in both Tuvan and Buryat. It was found that in Kyzyl, there is no significant difference in the linguistic landscape between central and peripheral areas. In Ulan-Ude, however, bilingualism as prescribed in the law can be observed mainly in the city center, with most of the signs in Russian.This is due to the higher concentration of state institutions, attractions, and cultural facilities in the city center, in an effort to comply with legal requirements, and the strategies of private businesses seeking to capitalize on the national brands and cuisine of the Republic. These similarities are not unique to Kyzyl or Ulan-Ude but are also found in the capitals of other republics in Russia. The potential for tourism, economic development, and identity is still waiting to be realized. Currently, «leveled» landscape features do not accurately reflect the cultural and linguistic diversity of a multi-ethnic country and do not contribute to the tourist attraction of these regions.
Keywords: linguistic landscape; Kyzyl; Ulan-Ude; language policy; law on languages; Tuva; Buryatia; Tuvan language; Buryat language; Russian language